An Evaluation of Consumer Awareness in Rural Markets - Krishna Mohan Naidu, Y. (Indian Journal of Marketing, 2004)
This paper deals with the extent of awareness in the rural markets of India. It presents the "Gold" available in this steadily growing market, which has been going great guns since the 1980's and is now bigger than the urban market for both FMCG's and durables. (The former with 53 percent share and the latter with 59 percent of total market.) The annual size of the rural marketing value terms is currently estimated at around Rs. 50,000 Crore for FMCG's, Rs. 5000 Crore for durables, Rs. 45000 Crore for Agri Inputs and implements and Rs. 8000 Crore for automobiles. A rural Consumer has proved to be very potential in terms of purchasing power though he is branded as illiterate by the census definition. He is not at all unintelligent but quite intelligent as is proved in this study. The study is an empirical research based on survey method. The data has been collected through a questionnaire. The survey is intended to seek information about the buying experiences of those rural consumers who have been widely purchasing goods and services. Ranga Reddy Dist. in Andhra Pradesh has been chosen for the study. Ten villages have been selected for this purpose. Agriculturists, Businessmen, Professionals, Homemaker's have been included in the sample. Altogether, a sample of 125 consumers has been selected for the study.